Effect of nitrogen deficiency on the physiology and biochemical composition of microalga Scenedesmus rotundus‐MG910488. (6th November 2019) - Dixit, Rishibha; Singh, Surendra; Singh, Ajeet
Abstract: The present investigation ascertains the impact of gradient concentrations of sodium nitrate on the physiology and biochemical composition of isolated microalga Scenedesmus rotundus ‐MG910488. The concentrations of nitrate were selected as 0, 3.5, 7.0, 10.5, 14.0, and 17.6 mM/L in BG11 medium. The lower concentrations of nitrogen were found to be significantly decreasing the cell count and photosynthetic activity in the microalga as well as changing cell morphology. The amount of biomass, its productivity and lipid yield were significantly affected. The highest biomass of 689.15 ± 14.27 mg/L was achieved in the concentration of 17.6 mM/L with the biomass productivity of 38.28 ± 0.78 mg/L. The highest lipid accumulation of 41.46 ± 1.94% dry‐cell weight was obtained at a concentration of 3.5 mM/L, whereas the lowest lipid accumulation of 29.22 ± 1.65% at the concentration of 17.6 mM/L sodium nitrate. The fatty acid composition determines the quality of the fuel, so the characterization of fatty acid methyl esters (FAMEs) was performed by GC, and the assessment of methyl esters of fatty acid confirmed the existence of palmitic acid, oleic acid, and linoleic acid, which are essential components suitable for biodiesel production. FTIR confirms the presence of FAME components by estimating the bending and stretching of functional groups.